PEDOT: Nafion Coated Microelectrode Biosensor for in Vivo Monitoring of Glutamate Release in Brain. (2017) - Ganesana, Mallikarjunarao; Trikantzopoulos, Elefterios; Venton, B. Jill
Abstract: L-Glutamic acid is one of the most prevalent excitatory signalling molecule in the central nervous system, plays a crucial role in a wide variety of brain functions such as memory, learning and neurological disorders like stroke, epilepsy and several other neurodegenerative diseases. In this study, we report on the design and development of an amperometric microelectrode based glutamate oxidase biosensor for real-time monitoring of L-glutamate in vivo in the mammalian brain. A Nafion and poly (3, 4-ethylenedioxythiophene) (PEDOT) containing polymer composite has been electropolymerized onto 50 μm Pt wire to act as a permselective membrane to selectively block common interfering substances in physiological conditions. In the second step, a mixture of glutamate oxidase entrapped in a biocompatible chitosan matrix was casted onto the surface of a Pt microelectrode. In the final step, ascorbate oxidase was coated onto the microelectrode to eliminate almost completely of any interference from high levels of extracellular ascorbic acid present in brain tissue. L-glutamate measurements were performed amperometrically at an applied potential of 0.6 V vs Ag/AgCl. The miniaturized microelectrode biosensor showed a rapid steady state response to L-glutamate within 2 s. The biosensor also exhibited a very good linear dependence on the concentration of L-glutamate with a high sensitivity and excellent storage stability. We will discuss in detail, the biosensor fabrication and characterization together with performance characteristics and in vivo testing in intact rat brain tissue.